Generex PUBG event tournament organized by Sports Science and Recreation diploma students / Ummi Kalthum Mohd Mokhtar - Mohd Mokhtar, Ummi Kalthum (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2021)
On 4th and 5th June 2021, the PUBG (Player Unknown's Battlegrounds) event tournament was organized by Sport Science and Recreation diploma students. This event intended to help students handle the elemental activities sportsmanship, team spirit, cooperation, and lots more. The programmer was in line with the main vision of the Faculty of Sports and Recreation Science to be the centre of excellence and leadership in the field of sports, sports management and recreation superior, ethical and world class.